Cancer ecology and evolution: positive interactions and system vulnerability. Issue 17 (October 2019) - Adler, Frederick R.; Gordon, Deborah M.
Abstract: Parallels of cancer with ecology and evolution have provided new insights into the initiation and spread of cancer and new approaches to therapy. This review describes those parallels while emphasizing some key contrasts. We argue that cancers are less like invasive species than like native species or even crops that have escaped control and that ecological control and homeostatic control differ fundamentally through both their ends and their means. From our focus on the role of positive interactions in control processes, we introduce a novel mathematical modeling framework that tracks how individual cell lineages arise and how the many layers of control breakdown in the emergence of cancer. The next generation of therapies must continue to look beyond cancers as being created by individual renegade cells and address not only the network of interactions those cells inhabit but also the evolutionary logic that created those interactions and their intrinsic vulnerability.